Determinants of Brand Loyalty through Customer Experience and moderated by Government Regulation in Indonesian Television - Donny Irawan; Sukesi Sukesi; Aminullah Assagaf (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study aims to analyze the determinants of brand loyalty strategy through customer experience, moderated by government regulation, in the television industry in Indonesia. Methodology/approach: This research employs a quantitative approach, with a population of 7,346,149 television viewers and a sample of 320 respondents selected using proportional sampling techniques. Data analysis was conducted using Structural Equation Modelling (SEM) with SmartPLS software. Results/findings: The findings are expected to demonstrate that business separation significantly influences customer experience, which subsequently strengthens brand trust and loyalty among television audiences. Furthermore, government regulation functions as a moderating variable that may either strengthen or weaken the relationships among variables, depending on the level of policy intervention in the television industry. Conclusions: Technological innovation and television quality content have a significant effect on customer experience, while AI-driven personalization and television quality content have a significant impact on brand loyalty. However, AI Driver Personalization and Technological innovation did not significantly affect brand loyalty. Limitations: Because the study used a quantitative cross-sectional survey that captures data at a single point in time, it cannot establish causal relationships or assess how constructs like customer experience and brand loyalty evolve over time, limiting causal inference in the rapidly changing television and media landscape. Contributions: This study contributes to the marketing management literature, particularly in the context of branding strategy and consumer behaviour within the media industry.